Evaluation of Organic Amendments Using Poultry Manure for the Improvement of Physical and Physico-chemical Properties of Theri Soil - E. Indira; B. Annadurai (Archives of Current Research International, 2016)
To evaluate the effect of different Organic amendments including Poultry and their different proportions on various physico-chemical and physical properties on theri soil. Investigations were carried out on the surface (15 cm depth) of soil samples were collected from the village of Punnai Nagar (Kachanavillai) in Tuticorin district, Tiruchendur Taluk, Tamilnadu. The experiment s were carried out during 2014(Oct) to 2015(Jan) was laid out in Pot culture with 10 treatments and 3 replications. All the amendments were applied and wetting with water regularly for 90 days without allowing them to get dried. After 90 days measurements were made. The result revealed that the use of organic amendment will increases NPK, Water holding capacity, Pore space, EC, Organic Carbon and decreased pH, bulk density, Particle density, Hydraulic conductivity. These changes in soil environment improved the soil fertility without affecting soil health.